2021
DOI: 10.1186/s12962-021-00309-0
|View full text |Cite
|
Sign up to set email alerts
|

What makes inequality in the area of dental and oral health in developing countries? A scoping review

Abstract: Background Equity in health is an important consideration for policy makers particularly in low and middle income developing country. The area of oral and dental health is not an exception. This study is conducted to explore the main determinants that make inequality in oral and dental health area in developing countries. Methods This was a scoping review applying the framework enhanced by Levac et al. Four databases of Scopus, PubMed, WOS and ProQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Low oral healthcare access is driven in part by the routine omission of oral healthcare from Universal Health Coverage [ 15 ], as well as the biomedical model of dentistry that incentivizes treatment-oriented oral healthcare, including fillings, crowns, and extractions, over prevention-oriented oral healthcare such as routine checkups, cleanings, application of fluoride varnish, and oral hygiene instruction [ 16 , 17 ]. This traditional model perpetuates the demand for highly-skilled dentists; however, in many LMICs, insufficient resources have been allotted to cultivate a prevention-oriented oral healthcare workforce and approach [ 10 , 18 ]. Finally, the rise in the overconsumption of sugary food products, specifically sugar-sweetened beverages, has exacerbated oral disease and has contributed greatly to the lack of improvement in global oral health [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low oral healthcare access is driven in part by the routine omission of oral healthcare from Universal Health Coverage [ 15 ], as well as the biomedical model of dentistry that incentivizes treatment-oriented oral healthcare, including fillings, crowns, and extractions, over prevention-oriented oral healthcare such as routine checkups, cleanings, application of fluoride varnish, and oral hygiene instruction [ 16 , 17 ]. This traditional model perpetuates the demand for highly-skilled dentists; however, in many LMICs, insufficient resources have been allotted to cultivate a prevention-oriented oral healthcare workforce and approach [ 10 , 18 ]. Finally, the rise in the overconsumption of sugary food products, specifically sugar-sweetened beverages, has exacerbated oral disease and has contributed greatly to the lack of improvement in global oral health [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SES in our data was focused on household income, which served as an economic indicator. Many socioeconomic determinants, including health inequality, income, ability to pay for services, and physical and geographical access to dental care services, have directly or indirectly correlated with dental health disparities [ 64 ]. We found that a significant number of children (~44%) with dental caries had access to dental services, which suggests the role of numerous socioeconomic constraints beyond geographical limitations in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, using national income as a proxy may result in this variation and therefore, suggested the individual level approach for future studies to tackle this issue. Moreover, lower middle-income countries have poorer oral health condition compared to upper-middle and high-income country groups, which may indicate the inequalities in oral health care (Bastani et al, 2021 ; Watt & Sheiham, 1999 ). Inequalities can stem from unjust provision of services or inappropriate access and become more pronounced by the fact that most dental treatment is funded by out-of-pocket payments (Listl et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%